Immunogenicity of the CoronaVac vaccine in children: a real-world study - Aguilar-Jimenez, Wbeimar; Rodriguez-Perea, Ana Lucia; Chvatal-Medina, Mateo; Velilla, Paula A.; Zapata-Builes, Wildeman; Monsalve-Escudero, Laura M.; Zapata-Cardona, Maria I.; Tabares-Guevara, Jorge Humberto; Rincón, Daniel S.; Hernandez, Juan C.; Tabares, Yulied; Lopez-Carvajal, Liliana; et al. (Frontiers in Immunology, 2024)
BackgroundDespite its proven effectiveness and safety, there are limited real-world data on CoronaVac’s immunogenicity in children, especially in lower-income countries, particularly for SARS-CoV-2 variants. We present a real-world study evaluating CoronaVac’s immunogenicity in Colombian children stratified by previous exposure to this virus.Methods89 children aged 3-11 years were enrolled (50 Non-Exposed and 39 Exposed). Saliva samples were collected every 15 days to monitor potential SARS-CoV-2 infection, and blood samples were taken at two and six months after vaccination, to evaluate immunogenicity. Total IgG and IgA antibodies were measured by ELISA, and neutralizing titers against B.1, Delta, Mu, and Omicron variants were assessed by plaque reduction assay. T-cells were stimulated with wild-type and Omicron peptide pools to analyze activation-induced markers, memory phenotype, cytotoxic molecules, and cytokine production by flow cytometry.FindingsCoronaVac was well tolerated, with only 7.8% infection incidence in both Exposed and Non-Exposed groups. It elicits a robust humoral response through IgG, IgA, and neutralizing antibodies against all variants. Despite waning, most participants maintained neutralizing titers ≥20 over time. CoronaVac also induced a polyfunctional cellular response against various strains, albeit reduced against Omicron, regardless of prior exposure. This response, characterized by IFN-γ/TNF-α and cytotoxic molecule production, was more pronounced in CD4+ than in CD8+ T-cells and remained detectable even after 6 months.InterpretationCoronaVac induces robust humoral and cellular immune responses against various variants in children, suggesting cross-recognition. However, these responses diminish over time, particularly in the context of variants, indicating the need for booster doses.